Perception of genital self-image, sexual quality of life and marital adjustment in infertile women - Yuksekol, Ozlem Dogan; Baltaci, Nazli; Yilmaz, Ayse Nur; Ulucan, Mihriban (Routledge Journals, Taylor & Francis Ltd, 2023)
LAY SUMMARY In this study, which was conducted to determine genital self-image, sexual quality of life and marital adjustment in infertile women, it was determined that low genital self-image negatively affected sexual life quality of life and marital adjustment. As the sexual life quality of women decreases, marital adjustment, agreement with their spouse and positive relationship style decrease. This study was conducted to determine the perception of genital self-image, sexual quality of life and marital adjustment in infertile women. The sample of this descriptive study consisted of 135 infertile women who applied to a university hospital in a provincial center in the east of Turkey between November 2020-January 2021. Data were collected using Personal Information Form, Female Genital Self-Image Scale (FGSIS),Marital Adjustment Test (MAT) and Sexual Quality of Life Questionnaire-Female (SQoL-F). Data analysis was performed using descriptive statistics, independent-samples t-test, one-way analysis of variance(ANOVA), Kruskal-Wallis test, Tamhane's T2 test, and Pearson's correlation analysis. FGSIS, SQoL-F, and MAT were found at moderate levels in the women who participated in the study (17.99 +/- 4.87, 65.58 +/- 26.77, 37.77 +/- 14.16, respectively). There was a moderate positive correlation between the total scores of FGSIS and SQoL-F, and a moderate and weak positive correlation between FGSIS and MAT and its sub-dimensions (p < 0.01).A moderate and weak positive correlation was found between SQoL-F and MAT and its sub-dimensions(p < 0.01).An increase in a positive genital self-image was associated with an increase in sexual life quality, marital adjustment, and agreement and positive relationship with the spouse. In addition, an increase in sexual quality of life was also associated with an increase in marital adjustment and agreement and positive relationship with the spouse. The vice versa could also be valid.
Keywords: Infertility; genital self-image; sexual life; marital adjustment